VRPTW Distribution Route Determination with Rigid and Flexible Time Window and Assignment Based on Number of Demand - Keynobi, Fikri; Wirdianto, Eri; Zidanne, Muhammad (Jurnal Sistem Teknik Industri, 2025)
Vehicle routing problems (VRP) are common in many companies and play an important role in distribution and logistics. Effective routing can significantly reduce expenses and increase customer satisfaction. The research entitled "Determining VRPTW Distribution Routes with Rigid and Flexible Time Windows and Assigning Based on the Demand Numbers" will solve the modified vehicle routing problem with time window (VRPTW) problem by considering constraints on vehicle capacity, delay times, penalty fees for delays, rigid and flexible time windows, and demand numbers. There is one origin depot for the company that will serve their 15 customers. The method used to overcome the problem is mixed-integer linear programming (MILP). In general, this research classifies time windows into three groups, namely rigid, flexible, and rigid and flexible. The time window model chosen is a rigid time window with a cost of IDR 561,965 and no customers are served late. The rigid time window model was chosen because no customers are served late and the cost difference is not significant or can be said to be very small compared to other time window models.